Effect of fertilization with N on height, number of leaves, and leaf area in banana (Musa AAA Simmonds, cv. Williams) - Torres-Bazurto, Jaime; Magnitskiy, Stanislav; Sánchez, Jaiver Danilo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The production of bananas (Musa AAA Simmonds, cv. Williams) for export in the Uraba area of Colombia represents economic and social benefits for the country, demanding improvements in agronomic practices, especially fertilization. The objective of this research was to evaluate plant height, leaf area and number of leaves in banana cv. Williams in two production cycles to adjust fertilizer recommendations according to the needs of the plants in the development phase. A sixth-generation crop was used, which was evaluated during five stages of development and two consecutive production cycles in 2011 and 2012. The multivariate approach was used for the analysis of variance of the repeated measures design, with two factors between subjects (fertilization and repetitions) and one intra-subject factor associated with the production cycle. The linear models were adjusted according to the phenological stage determined as when the vegetative structures were present, simultaneously evaluating responses in plant height, number of leaves, and leaf area. The effect of N doses on the developmental stages of the banana for production cycle and between cycles indicated that the doses of 321.8 and 483 kg ha-1 had the best yield. The dose of 483 kg ha-1 was the best one since it resulted in the highest plant growth.